2018
DOI: 10.1016/j.neuron.2018.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Kir4.1-Dependent Astrocyte-Fast Motor Neuron Interactions Are Required for Peak Strength

Abstract: SummaryDiversified neurons are essential for sensorimotor function, but whether astrocytes become specialized to optimize circuit performance remains unclear. Large fast α-motor neurons (FαMNs) of spinal cord innervate fast-twitch muscles that generate peak strength. We report that ventral horn astrocytes express the inward-rectifying K+ channel Kir4.1 (a.k.a. Kcnj10) around MNs in a VGLUT1-dependent manner. Loss of astrocyte-encoded Kir4.1 selectively altered FαMN size and function and led to reduced peak str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
119
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
3

Relationship

3
5

Authors

Journals

citations
Cited by 113 publications
(138 citation statements)
references
References 98 publications
2
119
0
1
Order By: Relevance
“…To ascertain if DNA hypermethylation may serve as a common mechanism of regulation of the Kcnj10 gene in injury we next evaluated the methylation status of Kcnj10 following trauma in a different CNS region. We and others have shown Kir4.1 expression is highest in caudal brain structures, particularly spinal cord gray matter (Kelley et al, ; Olsen et al, ; Olsen et al, ). During rodent postnatal development, Kcnj10 mRNA expression is higher in spinal cord relative to cortical regions and shows earlier developmental upregulation.…”
Section: Resultsmentioning
confidence: 60%
“…To ascertain if DNA hypermethylation may serve as a common mechanism of regulation of the Kcnj10 gene in injury we next evaluated the methylation status of Kcnj10 following trauma in a different CNS region. We and others have shown Kir4.1 expression is highest in caudal brain structures, particularly spinal cord gray matter (Kelley et al, ; Olsen et al, ; Olsen et al, ). During rodent postnatal development, Kcnj10 mRNA expression is higher in spinal cord relative to cortical regions and shows earlier developmental upregulation.…”
Section: Resultsmentioning
confidence: 60%
“…verified that Kir4.1 and Cx43 are bona fide substrates of N4-2. These data identify a new level of regulation of the major astrocytic K + channel Kir4.1 that operates posttranslationally, i.e downstream of previously characterized transcriptional regulation (Farmer et al, 2016;Kelley et al, 2018), to control astrocyte function. Disruption of such Kir4.1 regulations could be the bases of several neurological disorders, including amyotrophic lateral sclerosis and depression (Cui et al, 2018).…”
Section: Subsequent Biochemical (Figures 3f-3h) and Qrt-pcr Analysesmentioning
confidence: 70%
“…In our study, the quantification of astrocyte layer genes uniquely showed peaks and troughs of expression across the superficial-to-deep cortex, as well as differences across functionally distinct cortical areas. As prior studies show that regionrestricted astrocyte mRNA and protein expression are predictors of functions tailored to support of local neural circuits (8,30,31), astrocyte laminar genes indicate potential additional localized functions (32).…”
Section: Discussionmentioning
confidence: 89%